Safety of methotrexate in rheumatoid arthritis: a retrospective cohort study in clinical practice - G. Mennillo; R. Buono; D. Malesci; R. Vitiello; R. Tirri; G. La Montagna; G. Valentini (PAGEPress Publications, 2011)
Objective. To evaluate the treatment duration with MTX monotherapy or in association with DMARDs or anti TNFa inhibitors and the incidence and typology of adverse events (AE) occurred in rheumatoid arthritis (RA) patients. Methods. A retrospective large cohort study of RA outpatients, consecutively seen from January 2000 to June 2005 was performed. Study group were RA patients classified according to the 1984 ACR criteria for the classification of rheumatoid arthritis. The patients were divided in 3 groups according to the treatment regimen: MTX monotherapy, MTX in combination with DMARD or with anti TNFa agents. We analyzed 348 therapeutic cycles, 177 of whom using MTX monotherapy. Results. The 224 RA patients accumulated 800 person-years of follow up. Follow up for each of the groups was: MTX monotherapy 479.4 person-years, MTX in combination with DMARDs 244.5, or with anti TNFa inhibitors, 75.7 person- years. From the Kaplan-Meier analysis, the probability of patients remaining on treatment 5 years was 58.5 after starting MTX. The incidence of any AE was 8.87 per 100 person-years. From all, 69 (97.2%) AE were no severe. Among those, more frequently were observed at gastrointestinal tract (31%), liver (19.7%), skin (15.5%). Incidence of severe AE (lung adenocarcinoma, 1 case; pancreatitis, 1 case) was 0.25 per 100 person-years, occurring in patients taking MTX monotherapy or MTX in combination with DMARDs, respectively. Conclusions. These data confirm that methotrexate is well tolerated in clinical practice in the medium-long term. Nevertheless, the occurrence of severe AE require an accurate vigilance for methotrexate toxicity.